Rediscovering John Dewey How His Psychology Transforms Our Education - Li, Rex.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Palgrave Macmillan, 2020)
This book tries to trace Dewey$1 (Bs intellectual history from his early years to the end, focusing on the themes of psychology and the psychological aspect of education in Dewey$1 (Bs lifelong writing.The author mixed the discussion on Dewey$1 (Bs work with his life stories and shows readers how his ideas evolved over time. In turn, the book offers a critical review of his ideas in the areas of psychology and education. Lastly, it assesses Dewey$1 (Bs involvement in and impact on education. In short, it provides a comprehensive account of his legacy in psychology and education.s
(A) Early Years -- Boyhood and College Years -- The Lost Years -- Johns Hopkins Years -- (B) Psychology -- Young Dewey and Zeitgeist in Psychology -- A Psychological Manifesto and Philosophic Method -- Psychology, Reflex Arc Concept and the Birth of Functionalism -- Psychological Fallacy, How We Think, and Human Nature and Conduct -- (C) Education -- Chicago Years, My Pedagogic Creed and Resignation -- Educational Writings in Chicago -- Educational Writings in Columbia Years -- (D) Involvement in Education and Impact -- Dewey in China -- John Dewey and Progressive Education -- Late Writings on Education.
Keywords: Education$1 (BHistory.s; Education$1 (BPhilosophy.s; Educational psychology; History of Education; Educational Philosophy; Pedagogic Psychology